Epidemiology and morphology of female genital organs cancer in Kabardino-Balkaria during the period from 1990 to 2014 - A. A. Tkhakakhov (Опухоли женской репродуктивной системы, 2016)
The structure and trend of incidence, geographical prevalence, the comparative analysis and morphology of cancer of uterus, ovaries, vaginas and vulvas among inhabitants of Kabardino-Balkaria during 1990–2014 are presented. Rates of a gain of these new growths considerably exceed the all-Russian indicators especially concerning an endometrium carcinoma, but “rejuvenation” of diseases in Kabardino-Balkaria is not observed. Carcinomas of a body and a neck of a uterus meet among inhabitants of mountainous areas of the region than flat more often. Cancer tumors of endometrium and ovaries affect city dwellers, unlike a uterus neck more. The received results allow revealing actively patients at early stages of diseases, to hold medical examination and preventive events more effectively, to plan rational tactics of treatment of patients.